Pengembangan bahan ajar flipbook berbantuan Heyzine materi teks narasi kelas IV SD - Jannah, Latifah Roudhotul; Adikara, Fahmi Surya; Maharani, Siti Dewi (Universitas Muhammadiyah Magelang, 2025)
Research on the Development of Flipbook Teaching Materials Assisted by Heyzine Narrative Text Material for Grade IV SD adopts the ADDIE development model which is modified into four stages, namely Analyze, Design, Development, and Implementation. Data collection was carried out through three methods: interviews, expert evaluations, and response surveys. The research findings revealed a very high level of validity from various aspects: the material validity reached 93.75%, the media validity was 87%, and the assessment from the practicing teacher obtained a perfect score of 100%. Overall, this product has an average validity of 93% which falls into the highly valid category. Meanwhile, the practicality aspect of the product also showed very satisfying results: the individual trial achieved a perfect score of 100%, the small group trial obtained 89.2%, and the large group trial got 98.3%. The average value of product practicality reached 95.5% which is classified as very practical. Based on these results, it can be concluded that the flipbook teaching materials developed have very good quality and are feasible to be implemented in the learning process at school.